A modified choice experiment to examine willingness to participate in a Community Supported Agriculture (CSA) program among low-income parents. Issue 2 (3rd April 2020) - McGuirt, Jared T.; Jilcott Pitts, Stephanie B.; Hanson, Karla L.; DeMarco, Molly; Seguin, Rebecca A.; Kolodinsky, Jane; Becot, Florence; Ammerman, Alice S.
Abstract: There is a need to improve geographical and financial access to healthy foods for limited resource populations in rural areas. Community Supported Agriculture (CSA) programs can improve access to healthy foods in rural and limited-resource populations. However, research is needed to discern the most appealing conditions for a CSA (e.g. price, frequency, food quantity) among rural, low-income customers. The goal of this study was to understand low-income consumers' preferences related to participation in a CSA program, considering price, frequency, food quantity and accessibility (e.g. distance) conditions. A modified exploratory choice experiment exercise was embedded within in-depth interviews to examine willingness to participate in CSA under a variety of conditions among 42 low-income adults with at least one child in the household in North Carolina, New York, Vermont and Washington. Willingness to participate in a CSA under each condition was summed and compared across conditions. Results were stratified by race, number of children and household members and McNemar's test and Student's t -test were used to examine differences in willingness between conditions. Salient quotes were extracted to support themes related to each condition. Our analysis suggests that the ideal CSA would be a full-sized share of eight to nine items of mixed variety, distributed every other week, priced at less than US$15, no more than 10 min further than the supermarket (SM) from their home and preferably less expensive but no more than 20% more expensive than SM prices. CSAs interested in reaching rural low-income populations may benefit from considering these consumer-level preferences.